Dielectric Loaded Antenna With Conformal Waterbolus and Improved SAR for Hyperthermia Treatment of Localized Superficial Cancer - Rahul Choudhary; Kavitha Arunachalam (IEEE Access)
Selective increase in tumor temperature to 40 – $44~^{° }$ C during hyperthermia (HT) treatment is known to improve cancer treatment outcomes. However, existing HT applicators widely reported for large area diffused superficial cancers have challenges in selectively heating localized superficial tumors of 2-3 cm diameter located at curved surfaces of body. In this work, we report a compact water loaded 434 MHz antenna with 13.68 cm2 aperture area and an integrated conformal water bolus for HT treatment of small localized superficial cancers. The conformal water bolus was designed to provide good surface contact with the contoured tissue surface. Applicator power deposition and heating characteristics were characterized in phantoms as per the guidelines for superficial HT devices. The fabricated applicator has >98% power coupling at 434 MHz with 16.10 MHz bandwidth, 21.00 cm2 EFS, and 3.00 cm effective penetration depth in planar layered phantom. Thermal penetration depth and effective field size of 3.00 cm and 25.20 cm2, respectively measured in phantom demonstrate localized heating characteristics. Localized heating with >96% power coupling at 434 MHz was observed in cylindrical tissue phantoms and contoured surfaces of ex-vivo chicken and bovine tissues. It is concluded that the proposed applicator could be used for HT treatment of small localized superficial cancers.